1996
DOI: 10.1128/aac.40.1.186
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of vancomycin in adult cystic fibrosis patients

Abstract: Although the depositions of many antibiotics are altered in cystic fibrosis patients, that of vancomycin has not been studied. To assess vancomycin pharmacokinetics, 10 adult cystic fibrosis patients were given a parenteral dose of vancomycin (15 mg/kg) during the first 72 h of hospitalization for acute bronchopulmonary exacerbation. Blood samples were obtained at 0, 1, 1.25, 1.5, 2, 3, 4, 6, 8, 12, 15, and 24 h. The mean (standard deviation) weight, measured creatinine clearance, and Taussig clinical score we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
3
28
0
2
Order By: Relevance
“…when calculated. a References for pharmacokinetic and dosing information were as follows: tobramycin [8], chloramphenicol [9], rifampicin [10], penicillin G [11], vancomycin [12], ciprofloxacin [7], and other quinolones [13]. b The longest dosing interval was calculated by DI Ā¼ t 1=2 Ā£ log 2 Ć°C max =MPCƞ, where t 1/2 is the half-life of the plasma drug concentration.…”
Section: Resultsmentioning
confidence: 99%
“…when calculated. a References for pharmacokinetic and dosing information were as follows: tobramycin [8], chloramphenicol [9], rifampicin [10], penicillin G [11], vancomycin [12], ciprofloxacin [7], and other quinolones [13]. b The longest dosing interval was calculated by DI Ā¼ t 1=2 Ā£ log 2 Ć°C max =MPCƞ, where t 1/2 is the half-life of the plasma drug concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Paper-based medical records prior to 2007 were also examined for IVā€“AG and vancomycin dosing data. Vancomycin was included in the review because it can potentiate the cochleotoxicity of AGs (7, 19, 37ā€“40), and is typically given to patients colonized with methicillin-resistant Staphylococcus aureus (MRSA) as clinical standard of care (41). All participants treated with aminoglycosides received clinical doses of either tobramycin and/or amikacin, which appear to have equivalent ototoxic potential, as reported previously (42ā€“44).…”
Section: Methodsmentioning
confidence: 99%
“…In one small study, 10 adult patients with CF demonstrated vancomycin pharmacokinetic values similar to those in healthy adults without CF. 8 However, pediatric patients with CF are known to have altered pharmacokinetic values compared with healthy pediatric patients. One trial of 67 children (mean Ā± S.D.…”
Section: Key Pointsmentioning
confidence: 99%